2015
DOI: 10.1074/jbc.m114.612986
|View full text |Cite|
|
Sign up to set email alerts
|

HdeB Functions as an Acid-protective Chaperone in Bacteria

Abstract: Background: Periplasmic chaperones HdeA and HdeB are involved in the acid stress response in Escherichia coli. Results: HdeB requires its folded and dimeric state to protect E. coli from protein aggregation at pH 4. Conclusion: HdeA and HdeB use different mechanisms to prevent periplasmic protein aggregation, allowing them to function over a broad pH range. Significance: This study furthers the understanding of how enteric bacteria counteract acid stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 35 publications
3
59
0
Order By: Relevance
“…We have recently shown that HdeB is active in both the prevention of aggregation and in facilitating the refolding of proteins at acidic pH [11] consistent with previous suggestions that HdeB functions as an acid activated chaperone [48]. We recently reported that HdeB functions at pH values higher than what is optimal for HdeA [11]; HdeB exhibits maximal in vitro chaperone activity at pH 4, whereas HdeA has optimal chaperone activity at pH 2. Our selections were done on ordinary, not deliberately acidic media, implying that HdeB also has chaperone activity at more neutral pH values.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…We have recently shown that HdeB is active in both the prevention of aggregation and in facilitating the refolding of proteins at acidic pH [11] consistent with previous suggestions that HdeB functions as an acid activated chaperone [48]. We recently reported that HdeB functions at pH values higher than what is optimal for HdeA [11]; HdeB exhibits maximal in vitro chaperone activity at pH 4, whereas HdeA has optimal chaperone activity at pH 2. Our selections were done on ordinary, not deliberately acidic media, implying that HdeB also has chaperone activity at more neutral pH values.…”
Section: Resultssupporting
confidence: 68%
“…Indeed, there is good evidence that DppA from Rhodobacter has chaperone-like activity [40], and HdeB from E. coli has recently been shown to function as a chaperone at the moderately acidic pH of 4 [11]. Moreover, there is preliminary evidence that OppA may have weak chaperone activity in vitro [12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while HdeA is chaperone-active under severe acid stress (e.g., pH <3), HdeB exhibits its highest chaperone activity at pH 4 [73]. Moreover, unlike HdeA, HdeB remains dimeric and apparently folded in its chaperone-active state, suggesting two rather distinct activation mechanisms for HdeA and HdeB [73].…”
Section: Acid-activated Chaperones: Defense Against Low Ph Stressmentioning
confidence: 99%
“…However, while HdeA is chaperone-active under severe acid stress (e.g., pH <3), HdeB exhibits its highest chaperone activity at pH 4 [73]. Moreover, unlike HdeA, HdeB remains dimeric and apparently folded in its chaperone-active state, suggesting two rather distinct activation mechanisms for HdeA and HdeB [73]. Recently conducted pH-dependent NMR studies suggest that changes in HdeB's intrinsic dynamic properties could contribute to its chaperone function at pH 4 [74].…”
Section: Acid-activated Chaperones: Defense Against Low Ph Stressmentioning
confidence: 99%